Was It About COVID-19 Vaccine Acceptance or Societal Culture and Livelihoods? A Case of The Kruger National Park Employees, South Africa - D, Raphela Tlou (Journal of Ecohumanism, 2024)
The study tested whether the employees at the Numbi Gate of the Kruger National Park (KNP). were influenced by community or conservation-related benefits to take the COVID-19 vaccine. The study involved 35 employees of the KNP including Game rangers, administration staff, and conservationists.This study was purely quantitative and used a structured questionnaire with predetermined answers and some open-ended questions and applied three Generalised Linear models from the R statistical Software to address the objectives of this study. However, in all the key questions, there was a deliberate space provided for an open-ended answer for the employees, but none of them mentioned conservation as their answers were fixed on their benefit. The study also showed that respondents who were eager to get vaccinated were driven by the prospect of maintaining their livelihoods rather than by conservation reasons as the majority reported fear of losing their tourist tips. The findings of this study provide critical insights into the factors that contributed to vaccine hesitancy among employees at KNP. The significant influence of social media and conspiracy theories highlights the challenges posed by misinformation in the digital age. This study therefore concluded that vaccine hesitancy was more influenced by employee benefits instead of conservation. (All tables and figures used for this study are original and were developed from the study data by the author).